Circulating antibody to renal collecting ducts in patients with hepatoma or renal-cell carcinoma. - Forbes, A P (1975)
An anti-kidney antibody was demonstrated by the indirect immunofluorescence method in the serum of patients with primary tumours of the liver or kidney. The distribution of fluorescence in rabbit kidney was consistent with that of antibody to collecting ducts. The anti-collecting duct antibody (anti-CDA) could be absorbed from serum by normal adult rabbit or human kidney tissue and by one of three specimens of renal-cell carcinoma tissue. Anti-CDA differed from anti-mitochondrial antibodies and from anti-liver/kidney microsomal antibody in the pattern of fluorescent staining obtained with rabbit kidney. Two-hundred sera from patients with cancer and other diseases and forty-three from healthy hospital personnel were tested for anti-CDA. Eleven of the twenty-five positive sera were from patients with primary cancer of the liver or urinary tract, and all but six of the remainder were from patients with tumours involving the liver or with liver disorders that may be associated with nodular hyperplasia or tumour.